2020
DOI: 10.1099/mic.0.000927
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional response of Fusarium oxysporum and Neocosmospora solani challenged with amphotericin B or posaconazole

Abstract: Some species of fusaria are well-known pathogens of humans, animals and plants. Fusarium oxysporum and Neocosmospora solani (formerly Fusarium solani) cause human infections that range from onychomycosis or keratitis to severe disseminated infections. In general, these infections are difficult to treat due to poor therapeutic responses in immunocompromised patients. Despite that, little is known about the molecular mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 70 publications
0
3
0
Order By: Relevance
“…The genus Candida is the most common fungus resulting in different invasive infections ( 27 ). Recently, human infections caused by F. oxysporum and F. solani (Neocosmospora solani ) have increased and become the second most common mold infections after aspergillosis ( 28 ). Although their mean relative abundance was too low (less than 2%) Aspergillus ( A. ruber ) and Rhizopus ( R. arrhizus ) were significantly more abundant in Group 2 than in Group 1 (p-values, 0.000).…”
Section: Discussionmentioning
confidence: 99%
“…The genus Candida is the most common fungus resulting in different invasive infections ( 27 ). Recently, human infections caused by F. oxysporum and F. solani (Neocosmospora solani ) have increased and become the second most common mold infections after aspergillosis ( 28 ). Although their mean relative abundance was too low (less than 2%) Aspergillus ( A. ruber ) and Rhizopus ( R. arrhizus ) were significantly more abundant in Group 2 than in Group 1 (p-values, 0.000).…”
Section: Discussionmentioning
confidence: 99%
“…Of particular interest is a cytochrome P450 gene described as a benzoate-4-monooxygenase, which showed significant overexpression (g8537). A previous study on antifungal response in Fusarium oxysporum and Neocosmospora solani found a benzoate-4-monooxygenase to be overexpressed following treatment with amphotericin b and posoconazole [38]. This gene, denoted CYP53, is a member of the family of CYP450 enzymes exclusive to fungi that are involved in phenolic detoxification.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it was reported recently that several genes of F. oxysporum and F. solani related to mechanisms of antifungal resistance such as ergosterol synthesis pathways, drug efflux pumps, response to oxidative stress, and cell wall biosynthesis, were differentially regulated upon the treatment with amphotericin B (AMB) and posaconazole (PSC) [102].…”
Section: Antifungal Resistance Mechanismsmentioning
confidence: 99%